2014
DOI: 10.1016/j.jms.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Traveling-wave deceleration of SrF molecules

Abstract: We report on the production, deceleration and detection of a SrF molecular beam. The molecules are captured from a supersonic expansion and are decelerated in the X 2 Σ + (v = 0, N = 1) state. We demonstrate the removal of up to 40% of the kinetic energy with a 2 meter long modular traveling-wave decelerator. Our results demonstrate a crucial step towards the preparation of ultracold gases of heavy diatomic molecules for precision spectroscopy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 28 publications
2
57
0
Order By: Relevance
“…The acceptances are almost equal in both the longitudinal and transverse directions, which appears to be particularly advantageous for experiments that are designed to spatially trap the molecules at the end of the decelerator. Both traveling-wave Stark [24,25] and Zeeman [26][27][28][29] decelerators have been successfully demonstrated. Recently, first experiments in which the decelerated molecules are subsequently loaded into static traps have been conducted [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The acceptances are almost equal in both the longitudinal and transverse directions, which appears to be particularly advantageous for experiments that are designed to spatially trap the molecules at the end of the decelerator. Both traveling-wave Stark [24,25] and Zeeman [26][27][28][29] decelerators have been successfully demonstrated. Recently, first experiments in which the decelerated molecules are subsequently loaded into static traps have been conducted [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that these systems could be used to measure classes of P-violating electroweak interactions that are difficult to access otherwise [77,78], such as those due to nuclear anapole moments and axial hadronic-vector electronic electroweak couplings [79]. Results in this direction are expected by ongoing experiments in the DeMille and in the Hoekstra groups [80,81].…”
Section: Parity Violationmentioning
confidence: 99%
“…Unfortunately in such atoms the weak effects are rather small, typically of relative order 10 −9 of the electromagnetic interaction. Atomic or molecular systems with rather large parity violating effects, such as in Yb atoms [11] or in SrF [12] molecules, can be very well exploited for measuring, e.g., anapole moments. In these cases differences between isotopes can be utilized and atomic or molecular theory are required with rather moderate precision.…”
Section: Atomic Parity Violationmentioning
confidence: 99%